Quesungual slash and mulch agroforestry system (QSMAS): Improving crop water productivity, food security and resource quality in the sub-humid tropics - Castro, A.; Rivera, M.; Ferreira, Oscar; Pavon, Jellin; García, E.; Amézquita Collazos, Edgar; Ayarza, Miguel Angel; Barrios, E.; Rondón, Marco Antonio; Pauli, N.; Baltodano, Maria Eugenia; Mendoza, B.; et al. (CGIAR Challenge Program on Water and Food, 2009)
The knowledge and principles generated by CPWF-PN15 confirm that QSMAS can be a model production system for implementing conservation agriculture to achieve food security and sustainable development in drought-prone areas of hillsides in the sub-humid tropics, while providing ecosystem services in the face of land degradation and climate change. As an adoptable option to replace the slash and burn traditional system, QSMAS can improve smallholder livelihoods through eco-efficient use and conservation of natural resources. Participatory validation activities suggest that the conservation agriculture principles embedded in QSMAS can be readily accepted by resource- poor farmers and local authorities in similar agroecosystems.